Evaluasi dan Perbaikan Rancangan Situs Web SMA Negeri 7 Bekasi menggunakan Metode Human Centered Design (HCD) - Tubagus Reza Fachlevi; Satrio Hadi Wijoyo; Prima Zulvarina (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMA Negeri 7 Kota Bekasi created a school website to maximize the use of technology in the digital era to provide services and information for students and the public during the covid-19 pandemic. The website is considered imperfect and less well known by the public. Users find it difficult to use the website because there is no search feature, some features are not working, also inconsistent user interface. Therefore it is necessary to carry out an usability evaluation using the HCD method, usability testing and the SUS questionnaire. Usability testing is carried out to get three assessment metrics,that are effectiveness, efficiency, and satisfaction. This test involved nine participants who were divided into three groups, that are potential students, students, and public. The first test was done on the website, resulting in effectiveness metric of 42.2%, efficiency metric of 0.014 goals/sec and satisfaction metrics by using the SUS questionnaire obtained a score of 42 where the score in the interpretation of SUS are ‘not acceptable' in acceptability category, grade 'F' and 'OK' rating. The second test was done on the prototype, resulting in effectiveness metric os 64.4%, efficiency metric 0.03 goals/sec and satisfaction metric obtained a SUS score of 73 where the score in the interpretation of SUS are ‘acceptable' in acceptability category, grade 'C' and 'Good' rating.